THE ASSOCIATION OF MOTHERS PERCEPTION AND HEALTH STATUS ON SUSTAINABLE MATERNAL HEALTH UTILIZATION IN TLOGOWUNGU REGENCY OF PATI, INDONESIA - Sulistiyowati, Dwi; Ulfa, Zuly Daima (Proceedings of the International Conference on Applied Science and Health, 2017)
Backgrounds: Indonesia is part of the contributing countries of maternal mortality (8800, 3%) (WHO, 2014). Indonesia cannot reach the Millennium Development Goal target by 2015 while the utilization of maternal health services in Tlogowungu is low compared to other regions. The objective of this research is tantamount the influence of mothers perception about self-health and health status toward sustainable utilization of maternal health services. Method: Quantitative research type, cross sectional design, postpartum mothers in districts Tlogowungu Pati Regency as many as 140 people. Statistical analysis using logistic regression. Results: Utilization of sustainable maternal health services by 15%. Respondents mostly used the services of pregnancy (K1 = 87.9%, K4 = 83.6%) and delivery of 99.3% but dropped out during the puerperium (16.4%). Conclusion: There is a significant effect of perception on personal health and health status on the sustainable utilization of maternal health services. Dissemination of information on sustainable utilization of maternal health services needs to be improved as well as partnering with educational institutions in the improvement of sustainable services.Â